2016
DOI: 10.1111/tpj.13265
|View full text |Cite
|
Sign up to set email alerts
|

EXA1, a GYF domain protein, is responsible for loss‐of‐susceptibility to plantago asiatica mosaic virus in Arabidopsis thaliana

Abstract: SUMMARYOne of the plant host resistance machineries to viruses is attributed to recessive alleles of genes encoding critical host factors for virus infection. This type of resistance, also referred to as recessive resistance, is useful for revealing plant-virus interactions and for breeding antivirus resistance in crop plants. Therefore, it is important to identify a novel host factor responsible for robust recessive resistance to plant viruses. Here, we identified a mutant from an ethylmethane sulfonate (EMS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 72 publications
5
40
0
Order By: Relevance
“…More recently, Hashimoto et al (2016) demonstrated that deficiencies in essential for potexvirus accumulation 1 ( EXA1 ) gene were present in a loss-of-susceptibility Arabidopsis mutant that did not support plantago asiatica mosaic virus (PlAMV; Potexvirus ) accumulation. EXA1 is an unannotated gene in plants, but contains a putative eIF4E-binding motif and a GYF domain, which binds to proline-rich peptides (Kofler and Freund, 2006).…”
Section: Promising Genetic Resources For Recessive Resistancementioning
confidence: 99%
See 4 more Smart Citations
“…More recently, Hashimoto et al (2016) demonstrated that deficiencies in essential for potexvirus accumulation 1 ( EXA1 ) gene were present in a loss-of-susceptibility Arabidopsis mutant that did not support plantago asiatica mosaic virus (PlAMV; Potexvirus ) accumulation. EXA1 is an unannotated gene in plants, but contains a putative eIF4E-binding motif and a GYF domain, which binds to proline-rich peptides (Kofler and Freund, 2006).…”
Section: Promising Genetic Resources For Recessive Resistancementioning
confidence: 99%
“…EXA1 is an unannotated gene in plants, but contains a putative eIF4E-binding motif and a GYF domain, which binds to proline-rich peptides (Kofler and Freund, 2006). Based on sequence comparisons with other related genes, EXA1 homologs are encoded in rice and tomato and are structurally related to human GIGYF2 protein (Hashimoto et al, 2016). T-DNA insertion of EXA1 gene, forming exa1-1 mutant, does not affect accumulation of CMV, TCV, or YoMV, but does suppress the accumulation of two distinct potexviruses other than PlAMV (Hashimoto et al, 2016).…”
Section: Promising Genetic Resources For Recessive Resistancementioning
confidence: 99%
See 3 more Smart Citations